Experiences of occupation-based practice: An Australian phenomenological study of recently graduated occupational therapists. (July 2019) - Di Tommaso, Amelia; Wicks, Alison; Scarvell, Jennie; Isbel, Stephen
Introduction: The call for occupational therapists to embrace occupation-based practice has increased in recent decades. Little is known about how occupational therapists perceive and implement occupation-based practice. This study aims to uncover the experiences of new and recent graduates using occupation in their practice. Method: A phenomenological design guided the development of semi-structured interviews. New and recent Australian occupational therapy graduates were interviewed about their experiences of occupation in their practice. Interview transcripts formed the data and themes were developed by thematic analysis. Findings: Eighteen occupational therapists were interviewed. Three main themes emerged from the data. Overall, graduates found it challenging to embrace occupation in their everyday practice, deciding it is more pressing to remediate impairments than to enable occupations. Some participants stated that occupation-based practice was unrealistic given the efficiency pressures of their practice environments. However, graduates felt that with more experience they would be able to implement occupation in their daily practice. Conclusion: Recently graduated occupational therapists in Australia find it challenging to consistently implement occupation in their daily practice. Confidence to apply occupation-based skills is an important factor for implementing occupation in practice. Some recent graduates are choosing impairment-based techniques over occupation-based practice.